Diastolic left ventricular function in relation to circulating metabolic biomarkers in a population study. (January 2019) - Zhang, Zhen-Yu; Marrachelli, Vannina G; Yang, Wen-Yi; Trenson, Sander; Huang, Qi-Fang; Wei, Fang-Fei; Thijs, Lutgarde; Van Keer, Jan; Monleon, Daniel; Verhamme, Peter; Voigt, Jens-Uwe; Kuznetsova, Tatiana; et al.
Aims: We studied the association of circulating metabolic biomarkers with asymptomatic left ventricular diastolic dysfunction, a risk-carrying condition that affects 25% of the population. Methods and results: In 570 randomly recruited people, we assessed in 2005–2010 and in 2009–2013 the multivariable-adjusted correlations of e' (early left ventricular relaxation) and E/e' (left ventricular filling pressure) measured by Doppler echocardiography with 43 serum metabolites, quantified by magnetic resonance spectroscopy. In 2009–2013, e' cross-sectionally increased (Bonferroni corrected p  ≤ 0.016) with the branched-chain amino acid valine (per one standard deviation increment, +0.274 cm/s (95% confidence interval, 0.057–0.491)) and glucose+the amino acid (AA) taurine (+0.258 cm/s (0.067–0.481)), while E/e' decreased ( p  ≤ 0.017) with valine (–0.264 (–0.496– –0.031)). The risk of developing left ventricular diastolic dysfunction over follow-up (9.4%) was inversely associated ( p  ≤ 0.0059) with baseline glucose+amino acid taurine (odds ratio, 0.64 (0.44–0.94). In partial least squares analyses of all the baseline and follow-up data, markers consistently associated with better diastolic left ventricular function included the amino acids 2-aminobutyrate and 4-hydroxybutyrate and the branched-chain amino acids leucine and valine, and those consistently associated with worse diastolic left ventricular function glucose+amino acid glutamine and fatty acid pentanoate. Branched-chain amino acid metabolism (–log10 p  = 12.6) and aminoacyl-tRNA biosynthesis (9.9) were among the top metabolic pathways associated with left ventricular diastolic dysfunction. Conclusion: The associations of left ventricular diastolic dysfunction with circulating amino acids and branched-chain amino acids were consistent over a five-year interval and suggested a key role of branched-chain amino acid metabolism and aminoacyl-tRNA biosynthesis in maintaining diastolic left ventricular function.